(untitled) (Journal of the College of Basic Education, 2022)
Many people think that translating children’s literature is an easy work; simple words and short sentences of the Source Language (SL) which can be easily rendered to the Target Language (TL). But the important idea is that most of the translation difficulties are encountered in both children and adult literatures. This paper will take the Arabic translation of Hugh Lofting’s The Story of Doctor Dolittle[1] as a case study. This story is selected to be the case study because it includes many cultural issues in the children’s literature. The study discusses the strategies the translator has adopted in the translation process. Furthermore, the study will examine whether the translator’s adopted strategies have achieved the targeted aims of the translation process or not!. [1]The Arabic translation is published under the name of "رحلات الدكتور دوليتل", but as the researcher looked out the original version, supposedly would be "The Voyages of Doctor Dolittle", the content of this story was totally different from the Arabic translation. The paper found out that the Arabic translation rendered "The story of Doctor Dolittle" not "The Voyages of Doctor Dolittle".